Principles of biomedical ethics - Beauchamp, Tom L. (Oxford University Press, 2013)
"Acclaimed authors Tom L. Beauchamp and James F. Childress thoroughly develop and advocate for four principles that lie at the core of moral reasoning in health care: respect for autonomy, nonmaleficence, beneficence, and justice. Drawing from contemporary research--and integrating detailed case studies and vivid real-life examples and scenarios--they demonstrate how these prima facie principles can be expanded to apply to various conflicts and dilemmas"--